New Marketing Strategy Proposal for Train Restaurant Activities Managed by PT Reska Multi Usaha - Mekarsari, Julia Kunti; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2014)
Abstract. PT. Reska Multi Usaha is one of the subsidiaries of PT. Kereta Api Indonesia (Persero) that focused on giving the service of restaurant on the train. As the company that responsible for the service on train, PT. Reska didn’t change much every years, that is why some of the sales is decreasing in some area. The issue also followed by new problem from system organization of preparation work inside the company that can lead to train delay schedule. To analyze the root cause of the problem that PT Reska faced the three analyses is being conducted; there are external analysis, internal, and customer analysis. After all the analysis the result that causing the decreasing sale in PT Reska is causes by four problem, that are unfocused customer condition, different perception, habitual buyer, and no promotion. After all the analysis, the recommendation that being proposed is modified the STP and marketing mix and based on all the analysis and the recommendation, the implementation plan also made to help the company to calculate the resource and timeline in implementing the proposed solution.  Keywords: Train Restaurant, Food Industry, Marketing Strategy.